Analysing the Determinants of Credit Risk for General Insurance Firms in the UK - Guglielmo Maria Caporale; Mario Cerrato; Xuan Zhang (Center for Economic Studies and ifo Institute (CESifo), 2016)
This paper estimates a reduced-form model to assess the credit risk of General Insurance (GI) non-life firms in the UK. Compared to earlier studies, it uses a much larger sample including 30 years of data for 515 firms, and also considers a much wider set of possible determinants of credit risk. The empirical results suggest that macroeconomic and firm-specific factors both play important roles. Other key findings are the following: credit risk varies across firms depending on their business lines; there is default clustering in the GI industry; different reinsurance levels also affect the credit risk of insurance firms. The implications of these findings for regulators of GI firms under the coming Solvency II are discussed.
Keywords: G22; C58; 330; insolvent; doubly stochastic; insurance; reinsurance